Student’s Feedback based Blended Teaching Approach for Effective Learning - Anwar, Faisal (International Association of Computer Science and Information Technology, 2011)
This paper demonstrates a blended teaching approach based on student’s online feedback in an engineering unit at Curtin University, Western Australia and shows how it enhances the overall learning outcomes. The student’s feedbacks are collected using a university-wide online survey system known as “eVALUate”-an evaluation instrument for measuring students’ perceptions of their engagements andlearning outcomes. Students are encouraged to put their feedback through eVALUate in each semester for their enrolled units. In this study, such eVALUate survey data was used for a Civil Engineering unit -Water Engineering 361 for two consecutive years 2008-2009. In 2008, the teaching was donemainly using traditional method and the overall student’s satisfaction and the learning outcomes were found to be below the university or faculty agreement. All the suggestions and criticisms in eVALUate were taken into consideration for improvement of the unit in the following year. In 2009, a blended teaching approach composed of traditional and e-learning system based on the student’s feedback was adopted. The eVALUate survey data in 2009 shows that the learning outcomes and the overall student’s satisfaction exceed the target of university and faculty agreement showing blended teachingapproach based on student’s feedback could provide satisfactory learning outcomes in an engineering unit.